Empowering Indonesian Vocational Students with Artificial Intelligence Awareness: Challenges and Career Opportunities - Suyahman, Suyahman; Prayitno, Kintung; Pratama, Genta; Biddinika, Muhammad Kunta; Yudhana, Anton (Universitas Teknokrat Indonesia, 2024)
Artificial intelligence (AI) has emerged as one of the most transformative and influential technological advancements, significantly impacting sectors like healthcare, finance, and education in the rapidly evolving digital era. However, vocational high school students often have limited knowledge about AI, primarily due to the superficial coverage of AI in their curriculum and the lack of resources and trained educators. This study aimed to assess the effectiveness of an intervention designed to enhance AI awareness and understanding among vocational high school students. A comprehensive program was implemented, involving initial assessments, interactive face-to-face training sessions, and facilitated group discussions. Descriptive analysis using statistical methods was employed to compare pretest and posttest data, revealing significant improvements in students' knowledge and attitudes towards AI. For example, the average score for the question